Performance evaluation of alumina nanofluids and nanoparticles-deposited surface on nucleate pool boiling phenomena. (January 2020) - Modi, Mihir; Kangude, Prasad; Srivastava, Atul
Highlights: Nucleate pool boiling with water and nanofluids on plain substrate surface. Water-based boiling experiments on nanoparticles-deposited surface. Performance evaluation of various working fluids and nanoparticles-deposited surface. Bubble dynamical parameters and heat transfer rates. Abstract: Single bubble-based nucleate boiling phenomena of water and alumina-water nanofluids (0.005 and 0.01 vol% concentrations) have been studied under nucleate pool boiling regime for two different superheat levels. While nanofluids-based boiling experiments have been performed on plain substrate surface, experiments with water have been conducted on plain as well as nanoparticles-deposited surfaces. For developing an understanding of the influence of nanoparticles, simultaneous measurements of bubble dynamic parameters as well as associated thermal gradients field have been made using non-intrusive rainbow schlieren optical technique. A direct comparison of water and nanofluids experiments revealed significant changes in bubble dynamic parameters such as reduction in bubble departure diameter and growth time, increase in departure frequency and wait time for the case of nanofluids. Thermal gradients field showed more spreading out of the superheat layer adjacent to the heater substrate due to the addition of nanoparticles in the bulk liquid. In a subsequent study, surface modification of the heated substrate has been realized in the form of deposition of nanoparticles during nanofluid-based boiling experiments. The nanoparticles that get deposited on the surface during long time boiling experiments lead to surface modifications. The resultant nanoparticle-deposited surface is employed as the heater surface for conducting pool boiling experiments with water. Results of these experiments have been compared with those conducted using plain (smooth) heated substrate. Similar trends have been observed in the bubble dynamic parameters for the experiments with water on nano-deposited surface vis-a-vis nanofluids on plain surface. Heat transfer partitioning study revealed that natural convection component reduces and evaporative heat transfer increases significantly in the presence of nanoparticles. Plausible mechanisms for the observed trends have been investigated and discussed.